Mechanistic insights into the role of calcium in the allosteric regulation of the calmodulin-regulated death-associated protein kinase - Li, Xiaolong; Li, Bo; Li, Jun; Yang, Mingyuan; Bai, Yushu; Chen, Kai; Chen, Ziqiang; Mao, Ningfang (Frontiers in Molecular Biosciences, 2022)
Calcium (Ca2+) signaling plays an important role in the regulation of many cellular functions. Ca2+-binding protein calmodulin (CaM) serves as a primary effector of calcium function. Ca2+/CaM binds to the death-associated protein kinase 1 (DAPK1) to regulate intracellular signaling pathways. However, how the mechanism underlying the influence of Ca2+ on the conformational dynamics of the DAPK1-CaM interactions is still unclear. Here, we performed large-scale molecular dynamics (MD) simulations of the DAPK1-CaM complex in the Ca2+-bound and -unbound states to reveal the importance of Ca2+. MD simulations revealed that removal of Ca2+ increased the anti-correlated inter-domain motions between DAPK1 and CaM, which weakened the DAPK1-CaM interactions. Binding free energy calculations validated the decreased DAPK1CaM interactions in the Ca2+-unbound state. Structural analysis further revealed that Ca2+ removal caused the significant conformational changes at the DAPK1CaM interface, especially the helices 1, 2, 4, 6, and 7 from the CaM and the basic loop and the phosphate-binding loop from the DAPK1. These results may be useful to understand the biological role of Ca2+ in physiological processes.